Cultural tourism in Latin America : the politics of space and imagery - Baud, Michiel, 1952-; Ypeij, Johanna Louisa (Latin America studies ;, 2009)
Cultural tourism has become an important source of revenue for Latin American countries, especially in the Andes and Meso-America. This book analyses its effects and the processes of cultural change it provokes in local societies.